2000
DOI: 10.1121/1.1289371
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of acoustic waves into rippled sandy seafloors

Abstract: The Helmholtz-Kirchhoff integral and the Kirchhoff approximation are applied to model the penetration of sound waves into rough sandy seafloors at grazing angles above and below the critical angle. As the seafloor of interest is anisotropic, emphasis is placed on simulating the response from a two-dimensional interface. The analytical development of the method is first presented, followed by numerical examples. Simulations and data acquired at sea are in very good agreement in the 2-15 kHz band [Maguer et al.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Maguer et al [5] made measurements in the 2-15-kHz range, and argued, based on modeling studies, that the subcritical penetration they observed below 5-7 kHz is due to the evanescent wave, while above 5-7 kHz it is due to rough surface scattering. These conclusions were strengthened by very recent analyses [15], [16]. Though arguments are accumulating on the importance of seafloor roughness for subcritical acoustic penetration, seafloor characterization has not been extensive in previous acoustic measurements.…”
Section: B Motivation: Basic Research Issuesmentioning
confidence: 96%
See 1 more Smart Citation
“…Maguer et al [5] made measurements in the 2-15-kHz range, and argued, based on modeling studies, that the subcritical penetration they observed below 5-7 kHz is due to the evanescent wave, while above 5-7 kHz it is due to rough surface scattering. These conclusions were strengthened by very recent analyses [15], [16]. Though arguments are accumulating on the importance of seafloor roughness for subcritical acoustic penetration, seafloor characterization has not been extensive in previous acoustic measurements.…”
Section: B Motivation: Basic Research Issuesmentioning
confidence: 96%
“…It went into a four-point moor on Oct. 16 and came out on Nov. 11. During this period, the R/V Seward Johnson supported a variety of diver-intensive acoustic and environmental measurements, and as many as 20 cables were deployed from ship to equipment on the bottom.…”
Section: Brief Chronology Of Sax99mentioning
confidence: 99%
“…[16][17][18][19][20] One of the mechanisms of enhanced penetration into the seafloor is the scattering by rough surfaces, which was modeled in references. [21][22][23] In addition, in two experiments, Sax99 (Ref. 24) and Sax04, 8 the primary cause of subcritical acoustic penetration was shown to be diffraction by sand ripples.…”
Section: Introductionmentioning
confidence: 94%
“…From this research, mechanisms of subcritical penetration into seafloors have been explained as being due to the scattering from surface roughness of sea bottom, 1-6 the generation of Biot's slow waves in the poroelastic bottom, 7,8 and the scattering of evanescent waves induced by volume inhomogeneities. 9,10 Among them, scattering from interface roughness has been regarded as a primary cause, 11,12 and has attracted a broad interest. In explaining their experimental result 11 (SAX99), Jackson et al provided the evidence that the primary cause for the observed subcritical acoustic penetration was the diffraction by sand ripples via Bragg scattering.…”
Section: Introductionmentioning
confidence: 99%
“…They gave a diffraction model using first order perturbation theory for sinusoidal ripples and presented a high cutoff frequency of the minus first order Bragg wave. Pouliquen et al 12 investigated the scattering from sand ripples by the Helmholtz-Kirchhoff integral and correctly predicted the coherent (Bragg) interference patterns. To test the existence of Bragg scattering waves, Lim et al 13 performed a set of tank experiments by making an artificial "rough" interface that consists of polystyrene beads floating on the boundary between two immiscible fluids.…”
Section: Introductionmentioning
confidence: 99%